NEWS IN BRIEF. (Times Higher Education Supplement, 2005)
Presents news and developments in higher education in Great Britain compiled as of May 2005. Issues on a student vote of no confidence in Graham Upton, vice-chancellor of Oxford Brookes University; Application of a female computer games programmer at Derby University; Exclusion of two universities from a survey of university income and bursaries for 2006 resulting from technical errors.